Inovasi Pelayanan Surat Izin Praktik (SIP) bagi Tenaga Kesehatan di Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu (DPMPTSP) Kota Cirebon - Bella Ivanna Hutajulu, Anna; Budi Utami, Sawitri (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2025)
Innovation in public services is an urgent need amidst the demands of society for fast, efficient, and transparent services. This study aims to analyze the innovation process of the Practice Permit (SIP) service for health workers carried out by the Cirebon City Investment and One-Stop Integrated Service Office (DPMPTSP). This innovation is designed to replace the manual system which tends to be slow, inefficient, and prone to non-transparency. The theory used in this study is the innovation process model proposed by Luecke (2003) which consists of five stages, namely Idea Generation, Opportunity Recognition, Idea Evaluation, Development, and Commercialization. The research method used is descriptive qualitative, with data obtained through in-depth interviews, observations, documentation, and literature studies. The informant determination technique used in the study was the purposive sampling technique with a total of 13 informants, including DPMPTSP officials and health workers in Cirebon City. The results of the study indicate that the process of creating digital-based SIP innovations has not been implemented optimally because there are still shortcomings in several dimensions of the study, namely budget limitations, complexity of inter-agency bureaucracy, limited human resources and lack of socialization to users. However, in its implementation, SIP innovation has succeeded in increasing the efficiency of permit issuance processing time as well as transparency and satisfaction for health workers. This study recommends increasing collaboration between agencies, special budget allocation, intensive human resource training and expanding socialization to optimize the process of creating SIP innovations.